2019
DOI: 10.1007/s00167-019-05452-z
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-associated stem cell transplantation is successful in treating talar osteochondral lesions

Abstract: Purpose Osteochondral lesions (OCLs) of the talus are a challenging and increasingly recognized problem in chronic ankle pain. Many novel techniques exist to try and treat this challenging entity. Difficulties associated with treating OCLs include lesion location, size, chronicity, and problems associated with potential graft harvest sites. Matrix-associated stem cell transplantation (MAST) is one such treatment described for larger lesions > 15 mm 2 or failed alternative therapies. This cohort study describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…9 A similar matrix plus BMAC technique, known as MAST, has also demonstrated promising outcomes in treating medium to large lesions, but without radiographic data or a control group. 15 There is also a lack of existing literature on the use of ECM-BMAC alongside OAT, though supplementing OAT with BMAC alone seems to lower the rate of postoperative cysts. 20 ECM and BMAC in combination may further improve the results of OAT by providing a structural scaffold, stem cells, and growth factors to encourage thorough cartilage repair around the OAT plug.…”
Section: Discussionmentioning
confidence: 99%
“…9 A similar matrix plus BMAC technique, known as MAST, has also demonstrated promising outcomes in treating medium to large lesions, but without radiographic data or a control group. 15 There is also a lack of existing literature on the use of ECM-BMAC alongside OAT, though supplementing OAT with BMAC alone seems to lower the rate of postoperative cysts. 20 ECM and BMAC in combination may further improve the results of OAT by providing a structural scaffold, stem cells, and growth factors to encourage thorough cartilage repair around the OAT plug.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported promising outcomes after autologous cell transplantation; however, most of the literature consists of smaller case series with wide heterogeneity [35][36][37][38][39].…”
Section: Cell And/or Matrix Transplantsmentioning
confidence: 99%
“…In the literature, these techniques were compared with each other, but no technique was found to be superior to another. 3,14,17,18,20,27 AMIC technique consists of bone marrow stimulation via microfracture, structural support via autograft application for filling the defective area, and application of potentially chondrogenic agents, such as commercially available collagen type I/III bilayer matrix. Therefore, AMIC has the advantages of being a single-step (unlike ACI/MACI), less expensive (unlike ACI/MACI or allograft applications) procedure 27 and avoids the difficulties like obtaining a matching allograft or knee-related donor site morbidity, which is a major concern for OATS.…”
Section: Introductionmentioning
confidence: 99%